2016
DOI: 10.5664/jcsm.5700
|View full text |Cite
|
Sign up to set email alerts
|

CBT-I Coach: A Description and Clinician Perceptions of a Mobile App for Cognitive Behavioral Therapy for Insomnia

Abstract: Study Objectives: This paper describes CBT-I Coach, a patient-facing smartphone app designed to enhance cognitive behavioral therapy for insomnia (CBT-I). It presents findings of two surveys of U.S. Department of Veterans Affairs (VA) CBT-I trained clinicians regarding their perceptions of CBT-I Coach before it was released (n = 138) and use of it two years after it was released (n = 176). Methods: VA-trained CBT-I clinicians completed web-based surveys before and two years after CBT-I Coach was publicly relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(86 citation statements)
references
References 36 publications
3
82
0
1
Order By: Relevance
“…Several MAs have been developed to monitor sleep. For example, the CBT-I Coach, 4 Sleepio, 7 Win-Win aSleep, 8 and SleepRate 9 applications were developed to track sleep or facilitate CBT-I. Previous pilot studies found that CBT-I Coach improved sleep in 4 patients with cannabisuse disorder 10 ; when used as an adjunct to CBT-I, the MA improved adherence and sleep outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Several MAs have been developed to monitor sleep. For example, the CBT-I Coach, 4 Sleepio, 7 Win-Win aSleep, 8 and SleepRate 9 applications were developed to track sleep or facilitate CBT-I. Previous pilot studies found that CBT-I Coach improved sleep in 4 patients with cannabisuse disorder 10 ; when used as an adjunct to CBT-I, the MA improved adherence and sleep outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Some examples of these apps include: CBT-i Coach http://t2health.dcoe.mil/apps/CBT-i (Kuhn et al 2016), Moodkit http:// www.thriveport.com/products/moodkit/, DBT Diary Card and Skills Coach http://www.diarycard.net/, and CBT Bariatric https://cbtbariatric.com/ (Zhang et al 2015). Public health information and internet-based self-care for the public are also sources of self-management.…”
Section: E-health Enablermentioning
confidence: 99%
“…[8,29] Other BITs are intended to be used as a component of care that is led by a provider ("adjunctive" BITs; e.g., the CBTi Coach mobile application as an adjunct to provider led cognitive-behavioral therapy for insomnia). [30] Since implementation research is focused on how practices are integrated into care settings, the level of provider integration with BIT use has critical implications for implementation outcome measurement. A description of the types BITs and how they vary according to different levels of provider involvement is given in Figure 1, adapted from work by Muñoz (2017).…”
Section: The Continuum Of Bit Health Servicesmentioning
confidence: 99%